Brand Identity Development Strategy for RM. Laksana - Jaka Syaugi; Gallang Perdhana Dalimunthe (Cv. Syntax Corporation Indonesia, 2026)
This research examines the development of brand identity strategies for RM. Laksana, a traditional Sundanese restaurant in Kuningan, West Java, that has been operating for more than 50 years. In the context of the food and beverage (F&B) industry that continues to grow in Indonesia, especially in West Java with a growth of 15.53% (y-o-y) in the third quarter of 2025, RM. Laksana faces challenges in building a strong brand identity in the midst of increasingly fierce competition. This research uses a qualitative approach with in-depth interview methods with restaurant owners and managers, direct observation, and document analysis. The findings of the study show that RM. Laksana has strategic assets in the form of a 50-year heritage of hereditary recipes, a commitment to quality raw materials (live fish and homemade spices), and strong family values. However, the restaurant faces the problem of using generic names that causes consumer confusion. The recommended strategy includes developing an authentic brand identity by positioning RM. Laksana as the